Studying the organizational structure effectiveness on the basis of internal communication analysis - Tatyana V. Shinkarenko (Ural State University of Economics, 2020)
Digital technologies are changing corporate communication due to the opportunity to make contact via e-mail, social networks and messengers, which leads to the transformation of a company’s organizational structure. At the same time, the organizational structure should guarantee the effective implementation of communicative functions. Methodologically, the research relies on organizational theory when declaring communication to be one of the main functions of an organization that allows managing the organization and ensuring low transaction costs of internal communications. The present article aims to assess the possibility of using traces of internal corporate communication to gauge the organizational structure’s effectiveness. The authors adopt statistical and mathematical methods, such as the construction of a communication graph, clustering and comparative analysis. We process server data on intra-domain communications of the organization, build a communication graph, and evaluate various parameters reflecting its stability and flexibility and influencing the organizational structure’s effectiveness. Based on the proposed indicators, the study assesses the level of communication efficiency of each element of the company’s structure. The results of the research exploiting non-traditional sources of information and approaches allow us to evaluate the correspondence between the organizational structure and the cluster structure of communications, as well as the sustainability of internal and external communication of each element.